HUBUNGAN POLA ASUH ORANG TUA TERHADAP KECERDASAN EMOSIONAL ANAK USIA 10-12 TAHUN - romdiyah; ika Purnamasari; Ari setyawati; Syafa Nur Azizah (Maternity and Neonatal : Jurnal Kebidanan, 2024)
Background: Children aged 10-12 years are starting to be better able to understand and manage emotions in a more complex way. One of the factors that influences emotional intelligence in children is parenting factors or parenting patterns. Objective: This research aims to determine the relationship between parenting styles and the emotional intelligence of children aged 10-12 years at SD N 1 Sikunang. Method: This research is a quantitative study with a cross sectional approach carried out at SD N 1 Sikunang involving 46 children aged 10-12 years who were taken using total sampling. This research instrument uses a questionnaire on Parenting Patterns and Emotional Intelligence. Data analysis used frequency distribution and Chi Square test.Results: The most dominant parenting style for children aged 10-12 years at SD N 1 Sikunang is authoritarian parenting (41.3%), with moderate emotional intelligence (43.5%). Based on statistical tests, it was found that there was a significant relationship between parenting patterns and children's emotional intelligence, value = 0.000 < = 0.05. Conclusion: There is a relationship between parenting styles and the emotional intelligence of children aged 10-12 years at SD N 1 Sikunang. It is recommended that further research add other factors such as parental education level and living environment.